2010
DOI: 10.1038/sj.bjc.6605984
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic biomarkers in squamous cell carcinoma of the anus: a systematic review

Abstract: Background:Recent decades have seen combination chemoradiotherapy become the standard treatment for anal squamous cell carcinoma (SCC). However, the burden of this disease continues to rise, with only 10% of patients with metastatic disease surviving >2 years. Further insight into tumour characteristics and molecular biology may identify novel therapeutic targets. This systematic review examines current prognostic markers in SCC of the anus.Methods:An extensive literature search was performed to identify studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 81 publications
0
31
0
Order By: Relevance
“…A recent systematic review examined 29 different biomarkers [22]. Tumour-suppressor genes p53 and p21 were the only biomarkers which were prognostic in more than one study.…”
Section: Personalised Medicinementioning
confidence: 99%
“…A recent systematic review examined 29 different biomarkers [22]. Tumour-suppressor genes p53 and p21 were the only biomarkers which were prognostic in more than one study.…”
Section: Personalised Medicinementioning
confidence: 99%
“…In a previous systematic review of 21 studies published before 2010, Lampejo et al identified 13 biomarkers associated with outcome in ASCC (Lampejo et al , 2010). Of these, only p53 and p21 were shown to have prognostic utility in more than one study, yet their value was not universally supported by the reported literature.…”
Section: Current Biomarkers Of Response To Chemoradiotherapymentioning
confidence: 99%
“…However, their effect on prognosis remains undetermined and are of only limited benefit in colorectal cancer. A recent trial showed anti-EGFR (Cetuximab) combined with chemoradiotherapy to be too toxic to deliver 52. In terms of treatment stratification, p16INK4a is also strongly associated with relapse in SCC of the anus and suggests targeting the EGFR in poor risk/recurrent anal cancer 5254.…”
Section: Diagnosismentioning
confidence: 99%